IIIM-941, a Stilbene Derivative Inhibits NLRP3 Inflammasome Activation by Inducing Autophagy - Ali, Mehboob; Gupta, Mehak; Wani, Abubakar; Sharma, Ankita; Abdullaha, Mohd; Kour, Dilpreet; Choudhary, Sushil; Bharate, Sandip B.; Singh, Gurdarshan; Kumar, Ajay (Frontiers in Pharmacology, 2021)
Aberrant activation of NLRP3 inflammasome has been implicated in several inflammatory diseases. Autophagy is one of the primary mechanisms that regulate NLRP3 inflammasome activity. In this study, we attempted to target NLRP3 inflammasome activity by a synthetic compound IIIM-941. We found that IIIM-941 inhibits ATP induced NLRP3 inflammasome by induction of autophagy through AMPK pathway in bone marrow derived macrophages (BMDMs) and J774A.1 cells. It was interesting to observe that IIIM-941 did not show any inhibitory activity against LPS induced pro-inflammatory cytokines TNF-α and IL-6. The anti-NLRP3 activity of IIIM-941 was significantly reversed when we attempted to block autophagy by using either pharmacological inhibitor bafilomycin A1or by using siRNA against AMPK. Further, we found that IIIM-941 downregulated the expression of NLRP3 and prevented the oligomerization of ASC to exert its anti-NLRP3 inflammasome effect in J774A.1 cells. We validated inhibitory activity of IIIM-941 against NLRP3 in three different mice models. The anti-inflammatory effect of IIIM-941 was highly significant in ATP induced peritoneal inflammation model. IIIM-941 was similarly effective in suppressing MSU induced IL-1β in the air pouch model of inflammation without affecting the levels of TNF-α and IL-6. Finally, oral efficacy of IIIM-941 was also proved in MSU indued foot paw edema model of inflammation in mice at 10 and 20 mg/kg (b.w.). The compounds like IIIM-941 can be explored further for the development of therapies against diseases such as Alzheimer’s disease and Parkinson’s disease, where hampered autophagy and NLRP3 activation play a crucial role in the pathological development.